Finding Refuge in Canada Narratives of Dislocation - Melnyk, George; Parker, Christina (Athabasca University Press, 2021)
Millions of people are displaced each year by war, persecution, and famine and the global refugee population continues to grow. Canada has often been regarded as a benevolent country, welcoming refugees from around the globe. However, refugees have encountered varying kinds of reception in Canada. Finding Refuge in Canada: Narratives of Dislocation is a collection of personal narratives about the refugee experience in Canada. It includes critical perspectives from authors from diverse backgrounds, including refugees, advocates, front-line workers, private sponsors, and civil servants. The narratives collected here confront dominant public discourse about refugee identities and histories and provide deep insight into the social, political, and cultural challenges and opportunities that refugees experience in Canada. Contributors consider Canada's response to various groups of refugees and how Canadian perspectives on war, conflict, and peace are constructed through the refugee support experience. These individual stories humanize the global refugee crisis and challenge readers to reflect on the transformative potential of more equitable policies and processes. Contributions by Howard Adelman, Irene Boisier Policzer, Shelley Campagnola, Matida Daffeh, Eusebio Garcia, Julia Holland, Bill Janzen, Katharine Lake Berz, Michael Molloy, Adam Policzer, Pablo Policzer, Victor Porter, Boban Stojanović, Cyrus Sundar Singh, and Flora Terah